Addendum to 'Gravitational deflection of light and massive particle by a moving Kerr–Newman black hole'. (23rd December 2016) - He, Guansheng; Lin, Wenbin
Abstract: The analytical formula for the second-order gravitational deflection angle of a relativistic massive particle propagating in the equatorial plane of a Kerr–Newman black hole is derived.